АКТИВНА, РЕАКТИВНА ПОТУЖНОСТІ ЯК КОМПОНЕНТИ МИТТЄВОЇ ПОТУЖНОСТІ КОЛА З ПЕРІОДИЧНИМИ СТРУМОМ ТА НАПРУГОЮ - Бялобржеський, О.В. (Інститут електродинаміки Національної академії наук України, 2018)
Using the trigonometric form of the Fourier transform for periodic currents and voltages, the components forming instantaneous power are calculated. For harmonic currents and voltages, power components are calculated in which the active, reactive and apparent powers are allocated, as well as the initial phase of the latter, as a harmonic function. Performing an analysis of periodic polyharmonic currents and voltages, instantaneous power expressions are obtained, reduced to a certain normalized form. Using the well-known concept of the distribution of polyharmonic power components, corresponding to the energy conservation law and the Telleggen theorem, the active and reactive components are determined in the existing representation. It is noted that in this case it is impossible to single out the full power. Based on known works, for its integral estimation of polyharmonic power its quadratic norm is used. References 7, figure 2, tables 3.